Chewing water apple (syzygium aqueum) as an effort to reduce plaque index - Nafisah, Haifa Wardah; Purnama, Tedi; Rikawarastuti, Rikawarastuti (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Teeth are important organs that need to be kept clean. Maintaining oral hygiene will reduce a person's risk of developing diseases related to the mouth. Dental plaque is a collection of microorganisms on the surface of the teeth in the form of biofilms that can affect the oral cavity system. How to remove plaque naturally with fresh and fibrous fruits can be a self-cleaning or natural cleaner for the layer that sticks to the surface of the teeth, because it can indirectly rub the surface of the teeth. Guava is one of the fruits that contains water and fiber. Objective: This study aims to analyze the plaque index before and after chewing water apple. Method: The research design used in this study was a quasi-experimental design with a pretest and posttest with one group design. The data collection technique was purposive sampling, as many as 35 respondents. The instrument used in this study was a plaque index with the Patient Hygiene Performance Index and data analysis using a paired sample test. Results: The results of this study showed that before chewing water apple, 25 respondents (71.43%) were in the poor category and after chewing water guava, 34 respondents (97.14%) were obtained. The difference in plaque index score before chewing water apple was 2.1 while after chewing water apple was 1.1, with p=0.02. Conclusion: There was a decrease in plaque index before and after chewing water apple as evidenced by p<0.05